Bilateral Anophthalmia in Feline - Andrade, Ana Claúdia de Souza; Rey, Laisa Marina Rosa; Santos, Isabela Carvalho dos; da Silva, Lucas Lima; Charnovski, Sarah Gabriella Delallo; Merlini, Natalie Bertelis; Gonçalves, Daniela Dib (Acta Scientiae Veterinariae, 2021)
Background: Anophthalmia is a rare, congenital condition, defined as the complete absence of the eye bulb due to inadequate growth of the vesicle or optic dome. The malformation can be primary (in the absence of complete), secondary (in the presence of only residual tissue), or degenerative (in which the eye begins to form, but for some reason, it begins to degenerate). This condition is rare in dogs, cats, cattle, and sheep. Microscopic evaluation of orbital tissue for identification is always recommended. The aim of this study was to report a case of bilateral anophthalmia in a domestic cat. Case: A feline male, healthy, Maine Coon breed with 60 days of life was attended at the one veterinary private clinic. The cat, negative for FIV and FeLV, was born in a commercial cattery, belonging to his mother’s third litter, healthy litter with the exception of this feline. He arrived with a complaint of not opening his eyelids, like the rest of the litter. In the clinical examination, it was found the normality of vital signs, absence of other visible anatomical abnormalities, only the ocular region was observed with closed eyelids. The initial suspicions were anophthalmia and microphthalmia. The patient was referred for an ocular ultrasound, which showed the complete absence of the right and left eye bulbs. The right and left orbital cavities had only a volume of soft, amorphous, and predominantly homogeneous tissue. After the ultrasound report, the patient underwent a surgical procedure to remove a fragment of tissue from the eye socket, which was sent for histopathological examination to confirm anophthalmia and discard the differential diagnosis of microphthalmia. Microscopy revealed immature, epithelial, and glandular tissue in the middle of discrete and moderate connective tissue, loosely arranged. In some fragments, cartilaginous tissue was also revealed. Thus, the histological findings are compatible with immature, pseudoformed tissues and without neoplastic characteristics. The diagnosis of secondary anophthalmia was reached with use of ultrasound and histological reports. Discussion: Congenital malformations in domestic cats are less frequent than in dogs, some of which are rare, and little reported. Secondary anophthalmia in the reported patient was confirmed by histological and ultrasound examination. Bilateral secondary anophthalmia is characterized by the absence of the eyeball, but with the presence of adjacent tissue. The animal was submitted to an ocular ultrasound examination and the complete absence of ocular bulbs was found. The differential diagnosis of microphthalmia was ruled out because there was no evidence of the eyeball. Microphthalmia is a common congenital ophthalmic disorder in veterinary medicine. Representative fragments were submitted to histopathological examination, where immature, epithelial tissue was found. In some fragments sent for analysis, cartilaginous tissue was observed. The histological findings are compatible with immature, pseudoformed tissues, thus verifying bilateral congenital anophthalmia in the reported animal. The clinical examination in these cases serves to ensure that the animal does not have any other congenital changes, allowing a favorable prognosis in puppies. Based on the information presented, the animal in this study has bilateral secondary congenital anophthalmia, with a favorable prognosis for the patient to live with certain normality, with quality and well-being.